[BP.01.05] IMPACT OF 24-H BLOOD PRESSURE MONITORING ON OBJECTIVE SLEEP DURATION AND FRAGMENTATION IN RESISTANT HYPERTENSIVE PATIENTS. (September 2017) - Bruno, R.M.; Di Galante, M.; Banfi, T.; Di Pilla, M.; Taddei, S.; Faraguna, U.
Abstract : Objective: 24-h ambulatory blood pressure monitoring (ABPM) is crucial for diagnosis of treatment-resistant hypertension (RH). However, repetitive cuff inflations during night might induce sleep deprivation and hamper physiological nocturnal BP fall. The study was aimed at investigating the impact of the ABPM on sleep duration and fragmentation in RH patients. Design and method: 20 RH patients and 13 healthy controls (HC) were recruited and underwent 7-day actigraphy and ABPM. The following parameters were calculated on the whole week and separately for the ABPM night: total sleep time (TSTtot and TSTABPM), wake after sleep onset (WASOtot and WASOABPM) and sleep efficiency (SEtot and SEABPM). Results: RH patients were older (63 ± 11 vs 27 ± 4 years, p < 0.001), had higher 24-h (135 ± 16/78 ± 16 vs 122 ± 11/74 ± 5 mmHg, p = 0.01 and p = 0.42) and nighttime BP (130 ± 17/72 ± 14 vs 106 ± 11/62 ± 7 mmHg, p < 0.001 for both) and a reduced dipping (6 ± 6 vs 18 ± 5%, p < 0.001) than HC. RH had a lower TSTtot than HC (6.4 ± 1.1 vs 7.5 ± 0.9 h, p < 0.01). TSTABPM was not reduced during the ABPM night in both groups (6.8 ± 1.3 and 7.7 ± 1.4, p = ns vs TSTtot for both). However, WASOABPM tended to be longer than WASOtot in RH (RH: 73 ± 34 vs 61 ± 29 min, p = 0.07; HC 30 ± 24 vs 27 ± 17 min, p = ns), and SEABPM thus tended to be reduced in RH (84.4 ± 7.2 vs 86.2 ± 7.2%, p = 0.09) but not in HC (93.7 ± 3.2 vs 93.9 ± 5.0 p = 0.88). None of the considered sleep parameters were correlated with 24h-BP in HC and RH. Conclusions: ABPM did not significantly influence objective sleep duration and only marginally induce sleep fragmentation, thus can be safely used for diagnosis of resistant hypertension.